1999
DOI: 10.1001/archfaci.1.3.191
|View full text |Cite
|
Sign up to set email alerts
|

Closure of Mucosal Defects Over Exposed Mandibular Plates Using Fibrin Glue

Abstract: Background: Mandibular plates may become exposed following radiation therapy, infection, and mucosal necrosis. This may lead to early removal of the mandibular plates with subsequent instability of bone fragments.Objective: To compare fibrin glue, a bioadhesive, with traditional sutures in closing mucosa over exposed mandibular plates in a cat.Design: Prospective matched-pairs analysis.Subjects: Nine cats were used, and each cat served as its own control.Intervention: Bilateral mandibular plates were fixed on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2002
2002
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 19 publications
0
7
0
Order By: Relevance
“…The cutaneous wound was not stitched and remained open but covered with excessive natural fibrin sealant that is further cross-linked to host tissue matrix as protective barrier for external microbial infiltration as well as accelerating the wound healing by its components of different growth factors (Gaboriau et al, 1999;Kjaergard et al, 1999;Bolliger-Stucki et al, 2000). In this model, a potent antiinflammatory effect of guamerin was observed in the semi-enclosed cutaneous wound, remained almost in an aseptic condition, until the 5th day of experiment.…”
Section: Discussionmentioning
confidence: 99%
“…The cutaneous wound was not stitched and remained open but covered with excessive natural fibrin sealant that is further cross-linked to host tissue matrix as protective barrier for external microbial infiltration as well as accelerating the wound healing by its components of different growth factors (Gaboriau et al, 1999;Kjaergard et al, 1999;Bolliger-Stucki et al, 2000). In this model, a potent antiinflammatory effect of guamerin was observed in the semi-enclosed cutaneous wound, remained almost in an aseptic condition, until the 5th day of experiment.…”
Section: Discussionmentioning
confidence: 99%
“…It has been used extensively in human surgery, including maxillofacial surgery. 69 Similar to its xenogenous counterpart, autologous fibrin sealants may be used as a hemostatic, but also as an promoter of bone graft healing. 65,66 It is especially useful for closure of extraction wounds or following cyst enucleation in patients with coagulopathies.…”
Section: Fibrin Tissue Adhesivementioning
confidence: 99%
“…Extensive experimental data on laparoscopic inguinal hernia repair (IHR) have shown that the efficacy of fibrin glue as a means of mesh fixation is comparable to that of traditional techniques [1-3, 12, 15, 20, 25-27]. Fibrin glue causes a chemotactic attraction and stimulation of fibroblasts that result in enhanced tissue integration, achieving biologic soft fixation [28,29]. Prospective data also suggest that use of fibrin sealant significantly decreases pain and bleeding complications by avoiding the penetrating trauma and resultant neurovascular injury seen with sutures and tacks [12,15,16,20,27,30,31].…”
Section: Introductionmentioning
confidence: 99%